Effectiveness of the transitional care model in total knee arthroplasty patients: A randomized controlled trial - Güllü, Ayla; Tosun, Betu (John Wiley and Sons Inc, 2024)
Aim: This study has aimed to assess the effectiveness of the transitional care model (TCM) on functional status, perceived self-efficacy and healthcare utilization in patients undergoing total knee arthroplasty (TKA). Method: This randomized controlled study was conducted between February and November 2021 in a public hospital. The study randomly assigned patients to either a 6-week ‘TCM’ program or usual care. The sample size was n = 70, with each group comprising 35 individuals. Patient outcomes, including self-efficacy, functional status and healthcare service readmission rates, were monitored for TKA patients. Results: Nursing care based on the ‘TCM’ was found to enhance functional status and increase the level of self-efficacy among TKA patients, leading to a decrease in healthcare service readmissions. Conclusions: The study recommends preparing patients and their families for the preoperative and postoperative processes. It emphasizes the importance of providing necessary training and consultancy services under the leadership of orthopaedic nurses responsible for TKA patient care, guided by the principles of TCM. © 2024 The Author(s). International Journal of Nursing Practice published by John Wiley & Sons Australia, Ltd.
Keywords: functional status; patient readmission; randomized trial; self-efficacy; total knee arthroplasty; transitional care model